Dispositional mindfulness is predicted by structural development of the insula during late adolescence. (August 2015) - Friedel, S.; Whittle, S.L.; Vijayakumar, N.; Simmons, J.G.; Byrne, M.L.; Schwartz, O.S.; Allen, N.B.
Highlights: Adolescence is a critical period for the development of self-regulatory abilities. The cultivation of mindfulness has been associated with improved self-regulation. We examined brain development and dispositional mindfulness in adolescence. Adolescents with higher levels of mindfulness demonstrated less thinning in the left anterior insula. Abstract: Adolescence is a critical period of development, in which the increasing social and cognitive demands of independence need to be met by enhanced self-regulatory abilities. The cultivation of mindfulness has been associated with improved self-regulation in adult populations, and it is theorized that one neurodevelopmental mechanism that supports this capacity is the development of the prefrontal cortex. The current study examined the neurodevelopmental mechanisms associated with dispositional mindfulness in adolescence. Using a longitudinal within-persons design, 82 participants underwent structural magnetic resonance imaging (MRI) assessments at approximately ages 16 and 19, and also completed self-reported measurements of mindfulness at age 19. It was hypothesized that adolescents who demonstrated greater thinning of frontal cortical regions between the age of 16 and 19 would exhibit higher dispositional mindfulness levels at age 19. Results indicated that, contrary to predictions, adolescents with higher levels of mindfulness demonstrated less thinning in the left anterior insula. By contrast, higher IQ was associated with greater thinning of the right caudal middle frontal and right superior frontal regions. The involvement of insula development in mindfulness is consistent with a direct role for this structure in managing self-regulation, and in doing so concords with recent models of self-referential interoceptive awareness.